Research on Performance of Asymmetrical Shutter Fins in Microchannel Heat Exchanger - Gou Weilong; Liu Yusheng; Feng Jiawang; Li Jiawei; Li Wanyong; Chen Jiangping (Zhileng xuebao)
In view of the uneven heat transfer and high wind resistance of traditional symmetrical louver fin heat exchangers, which are most commonly used in automobile heat pump air conditioners, six asymmetric louver fin structures were proposed. STAR-CCM+ software was used to numerically simulate the structure of asymmetric louver fins, and the change characteristics of the internal temperature and pressure fields of the heat exchanger under the corresponding four working conditions were studied, and the heat transfer factor j and resistance factor f of each fin were calculated. The results show that although the heat exchange of the new asymmetric louver fin B3 group is slightly reduced, it has a significant effect on the reduction of wind resistance. When the air inlet velocity is 4.5 m/s, the resistance factor f is reduced by 31.9%, the heat transfer of the entire fin is more uniform, and there is no obvious concentrated heat transfer part on the entire fin. This study also conducted experimental research on a new type of fin, and the results show that most of the errors between the experimental and simulation results are below 10%.